Dissolvable Base Scaffolds Allow Tissue Penetration of High‐Aspect‐Ratio Flexible Microneedles. Issue 13 (2nd August 2015) - Yagi, Satoshi; Yamagiwa, Shota; Kubota, Yoshihiro; Sawahata, Hirohito; Numano, Rika; Imashioya, Tatsuya; Oi, Hideo; Ishida, Makoto; Kawano, Takeshi
Abstract : Microscale needle technology is important in electrophysiological studies, drug/chemical delivery systems, optogenetic applications, and so on. In this study, dissolvable needle‐base scaffold realizes penetration of high‐aspect‐ratio flexible microneedles (e.g., <5 μm diameter and >500 μm length) into biological tissues. This methodology, which is applicable to numerous high‐aspect‐ratio flexible microneedles, should reduce the invasiveness and provide safer tissue penetrations than conventional approaches.